Pola Tashih Mushaf Al-Qur’an di Indonesia Benang Merah Institusi Pentashihan sebelum Tahun 1959 - Hakim, Abdul (SUHUF, 2014)
This paper describes the patterns of the correction of the Quran in Indonesia by taking samples from the Quranic handwriting and some printed Qur'an which were published before 1959. The year was the year of the establishment of the Institution of the Correction of the Quran which serves as the sole for all the Quran circulated in Indonesia. There are two pattens of the correction of the Quranic handwriting namely the correction at the time of rewriting and that of after rewriting. As for the printed Quran, there are two patterns: correction to the local religious institution and correction to the correctors which consist of the Quranic scholars. Keywords: Tashih (correction of the Qur’an), printed Qur’an, Standing Committe of the Correction of the Quran, ancient manuscript.